Lipidomics in Ulcerative Colitis Reveal Alteration in Mucosal Lipid Composition Associated With the Disease State. Issue 11 (11th May 2019) - Diab, Joseph; Hansen, Terkel; Goll, Rasmus; Stenlund, Hans; Ahnlund, Maria; Jensen, Einar; Moritz, Thomas; Florholmen, Jon; Forsdahl, Guro
ABSTRACT: Background: The onset of ulcerative colitis (UC) is associated with alterations in lipid metabolism and a disruption of the balance between pro- and anti-inflammatory molecules. Only a few studies describe the mucosal lipid biosignatures during active UC. Moreover, the dynamics of lipid metabolism in the remission state is poorly defined. Therefore, this study aims to characterize mucosal lipid profiles in treatment-naïve UC patients and deep remission UC patients compared with healthy subjects. Methods: Treatment-naïve UC patients (n = 21), UC patients in deep remission (n = 12), and healthy volunteers (n = 14) were recruited. The state of deep remission was defined by histological and immunological remission defined by a normalized TNF-α gene expression. Mucosa biopsies were collected by colonoscopy. Lipid analysis was performed by means of ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS-MS). In total, 220 lipids from 11 lipid classes were identified. Results: The relative concentration of 122 and 36 lipids was altered in UC treatment-naïve patients and UC remission patients, respectively, compared with healthy controls. The highest number of significant variations was in the phosphatidylcholine (PC), ceramide (Cer), and sphingomyelin (SM) composition. Multivariate analysis revealed discrimination among the study groups based on the lipid profile. Furthermore, changes in phosphatidylethanolamine(38:3), Cer(d18:1/24:0), and Cer(d18:1/24:2) were most distinctive between the groups. Conclusion: This study revealed a discriminant mucosal lipid composition pattern between treatment-naïve UC patients, deep remission UC patients, and healthy controls. We report several distinctive lipids, which might be involved in the inflammatory response in UC, and could reflect the disease state. Abstract : The lipidomic analysis of mucosal lipids in UC patients revealed disruption in lipid composition patterns in active and deep remission UC. Several lipids seem to be involved in the inflammatory processes in UC, and could reflect the disease state.